The differences in job satisfaction among employees in public and private enterprises in Serbia - Snežana Mihajlov; Velimir Dedić; Dobrica Radovanović; Nenad Mihajlov (Industrija, 2013)
The aim of this paper is to show the sector differences in job satisfaction among employees in Serbian enterprises. Based on the empirical and theoretical findings, it was shown that the employees in public enterprises in Serbia are more satisfied with their job than their counterparts in the private sector, which presents a general trend characteristic of countries where research of this type was carried out. In addition, it was pointed out to the general trend in preference of the employment of employees in public enterprises, that is, the abandonment of the private sector of the economy. It was shown that the effects of the economic crisis in the country, together with incomplete adjustment to the new market conditions in the field of labour and employment relations, determine job certainty as one of the most important factors in shaping employee satisfaction which contributes to decision making about staying in or leaving an organization.